The politics of provocation : participation and protest in Israel - Wolfsfeld, Gadi. (Albany, N.Y. : State University of New York Press, 1988)
Annotation A straightforward presentation in which theoretical/conceptual orientation is both novel and grounded in sound testing with extensive data. Annotation copyrighted by Book News, Inc., Portland, OR.
The changing political culture of Israel -- The analytical framework -- Who, what, and why: explaining individual participation -- Beyond the numbers -- Explaining collective action -- Beyond the collection numbers -- Outcomes of collective action.
Includes bibliographical references (pages 195-200) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Israel -- Politics and government; Political participation -- Israel; Radicalism -- Israel; Participation politique -- Israël.; Radicalisme -- Israël.; Israël -- Politique et gouvernement; POLITICAL SCIENCE -- Political Process -- General; Political participation; Politics and government; Radicalism; Israel; Politische Beteiligung; Israel